2017
DOI: 10.18321/ectj497
|View full text |Cite
|
Sign up to set email alerts
|

Application of POSS Nanotechnology for Preparation of Efficient Ni Catalysts for Hydrogen Production

Abstract: POSS (polyhedral oligomeric silsesquioxanes) nanotechnology was applied for preparation of efficient Ni catalysts for hydrogen production through autothermal reforming of methane (ATR of CH 4 ). The novel metal-POSS precursor [Nickel (II) -HeptaisobutylPOSS (C 4 H 9 ) 7 Si 7 O 9 (OH)O 2 Ni] of Ni nanoparticles was introduced into Ce 0.5 Zr 0.5 O 2 support with following calcination and reduction stages of activation. The peculiarity of the genesis of Ni/SiO 2 /Ce 0.5 Zr 0.5 O 2 nanomaterials and their characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…It was shown that modification of supports is an effective way to control the catalyst performance in reforming of fuels [24][25][26][27][28][29][30]. This study is devoted to the elucidation of the role of support composition in autothermal reforming of ethanol over Ni/Ce 1-x Gd x O y , Ni/Ce 1-x La x O y and Ni/Ce 1-x Mg x O y catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that modification of supports is an effective way to control the catalyst performance in reforming of fuels [24][25][26][27][28][29][30]. This study is devoted to the elucidation of the role of support composition in autothermal reforming of ethanol over Ni/Ce 1-x Gd x O y , Ni/Ce 1-x La x O y and Ni/Ce 1-x Mg x O y catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This study continues our works on optimization of catalyst performance through regulation of support characteristics [2,[29][30][31][32][33][34] and it is focused on the elucidation of the role of Ce…”
Section: Introductionmentioning
confidence: 58%
“…Cagelike metallasilsesquioxanes (CLMSs) are a popular class of metallacomplexes, adopting a kaleidoscopic variety of cage architectures. Such a structural variety endows CLMSs with a wide number of potential applications such as molecular magnets (including single molecule magnets and spin glasses) and objects with photophysical properties (including the first example of a CLMS-based luminescent thermometer). In the context of materials science, there are applications of CLMSs for the aggregation of functional extended structures (coordination polymers), ceramics, , anodes, , molecules for biomedical application, and flame retardants . CLMSs are widely applied in homo- and heterogeneous catalyses. , Recent reports involve activity in (i) hydrogen production, (ii) Chan–Evans–Lam (CEL) couplings, (iii) the hydroboration of ketones, (iv) CO 2 valorization, (v) the synthesis of bio-derived ethers, and (vi) oxidative amidation . Separately, we would like to mention a well-known activity of transition metal complexes in catalysis of the oxidations of hydrocarbons and alcohols involving the functionalization of C–H bonds. Furthermore, multicopper­(II) cores are among the most active oxidation catalysts. , Recently, an implementation of the alkaline metal ions rubidium and cesium has been applied for the design of unusual types of catalytically active CLMS frameworks. ,, Being interested in both of these directions [(i) design of potential oxidative catalysts and (ii) investigation of the influence of large alkaline metal ions on CLMS structure formation], we have performed detailed studies ...…”
Section: Introductionmentioning
confidence: 99%
“…32 CLMSs are widely applied in homo-and heterogeneous catalyses. 27,33−38 Recent reports involve activity in (i) hydrogen production, 39 (ii) Chan− Evans−Lam (CEL) couplings, 40 (iii) the hydroboration of ketones, 41 (iv) CO 2 valorization, 42 (v) the synthesis of bioderived ethers, 43 and (vi) oxidative amidation. 44 Separately, we would like to mention a well-known activity of transition metal complexes in catalysis of the oxidations of hydrocarbons and alcohols involving the functionalization of C−H bonds.…”
Section: ■ Introductionmentioning
confidence: 99%